2016
DOI: 10.1007/s10546-016-0157-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Characteristics of Roughness Sublayer Mean Flow and Turbulence Over a Realistic Urban Surface

Abstract: Single-point measurements from towers in cities cannot properly quantify the impact of all terms in the turbulent kinetic energy (TKE) budget and are often not representative of horizontally-averaged quantities over the entire urban domain. A series of large-eddy simulations (LES) is here performed to quantify the relevance of non-measurable terms, and to explore the spatial variability of the flow field over and within an urban geometry in the city of Basel, Switzerland. The domain has been chosen to be cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
96
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(118 citation statements)
references
References 82 publications
7
96
2
Order By: Relevance
“…The study features a spatial resolution of 1 m, which is unprecedented at this scale. Giometto et al (2016) found the same resolution to be sufficient to capture the relevant turbulence physics within a real urban roughness sublayer. However, the effect of grid resolution on the final result is not investigated in this work.…”
Section: Physical Setup For the Les Modelmentioning
confidence: 84%
“…The study features a spatial resolution of 1 m, which is unprecedented at this scale. Giometto et al (2016) found the same resolution to be sufficient to capture the relevant turbulence physics within a real urban roughness sublayer. However, the effect of grid resolution on the final result is not investigated in this work.…”
Section: Physical Setup For the Les Modelmentioning
confidence: 84%
“…This provides an understanding of the structures of turbulent flow and its interaction with SBF over urban‐like surface from a fundamental perspective. We note that uneven buildings or land use may impose a spatial contrast of dynamic and thermal forcing, which can influence the features of turbulent flow [e.g., Chen et al ., ; Giometto et al ., ]. Further introducing complex surface with variable block's shape and/or height is a potential work in the future [ Jurelionis and Bouris , ].…”
Section: Configuration Of Numerical Model and Experimentsmentioning
confidence: 99%
“…Treating a wind farm as an enhanced surface roughness is perhaps the most common concept used to represent the atmospheric flow over turbines. Modelling of large-scale (in comparison to surface roughness) momentum-absorbing elements near the surface as enhanced surface roughness has counterparts in studies of flows over vegetated canopies and urban environments (Tseng et al 2006;Giometto et al 2016). Note that, in the above framework, the ABL is partitioned vertically, and is dependent on neglecting entrance effects and the formation of an internal boundary layer that would be prominent features in a flow over a realistic finite-sized wind farm.…”
Section: Introductionmentioning
confidence: 99%